The Methodology of Teaching Expressive Reading - Abilovna, Ramazanova (Indonesian Journal Publisher, 2025)
With the help of various pedagogical and methodological tools, the teacher facilitates the active learning of the language: selects the appropriate educational material for a given age, uses various teaching methods and techniques, organizes classes in the system. When choosing methods and techniques, the content of the program, the specifics of the concepts and ideas that need to be formed during training are taken into account. The article reveals that the methodology for teaching expressive reading includes several key aspects such as scene interpretation, role reading and staging literary works, and the principles of historicity and continuity of the methodology for teaching expressive reading and the application of modern educational methods throughout the lesson. As a result of the study, it was analyzed that the correlation between elements expressed by the strategic importance of creating expressive reading skills for the future development of students is used in theory and practice.